Hybrid models of higher education: Features and advantages - Elena Y. Kuznetsova; Olga V. Korableva (Russian Journal of Education and Psychology)
Background. The COVID-19 pandemic has shown that one of the most effective ways to ensure access to education, maintain social interaction and student engagement, despite geographical separation, is hybrid learning. A review of Russian and foreign literature revealed a common mistake of identifying it with mixed learning, which necessitated a thorough study of the issue. The conducted research allowed us to establish that hybrid learning is characterized by a number of problems, including personal incompatibility with the learning format, technical difficulties, the level of digital, informational, methodological and psychological preparedness of both teachers and students. The practical significance of the research is to contribute to solving the pedagogical problem of developing effective learning scenarios by forming the right approach to determining the essence of hybrid learning.